2010
DOI: 10.5664/jcsm.27827
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Reports of Sleep Problems in Non-Hispanic White, Hispanic, and African American Patients with Alzheimer Dementia

Abstract: Study Objectives: Sleep problems are common in persons with dementing illnesses and among the most stressful patient behaviors for caregivers. Although studies have shown differences in sleep across ethnic groups, little information is available on ethnic differences among persons with dementia. The purpose of this study was to investigate possible ethnic differences in sleep problems among patients with Alzheimer dementia. Method: Caregiver reports of 5 sleep-or circadian rhythm-related behavioral problems (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…These findings corroborate previous research with younger Māori adults (aged 20–59 years). Ethnic disparities with regard to sleep health could be associated with sleep disordered breathing, physical and mental health, or SEP [9,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate previous research with younger Māori adults (aged 20–59 years). Ethnic disparities with regard to sleep health could be associated with sleep disordered breathing, physical and mental health, or SEP [9,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, dysregulation of the clock also appears to contribute to disturbances of the sleep-wake cycles in individuals with Alzheimer's disease. These spontaneous night-time awakenings in patients with Alzheimer's disease are one of the most challenging issues for caregivers [ 42 ]. Likewise, individuals suffering from Huntington's disease exhibit clock-regulated disruption of neuroendocrine output, and of the sleep-wake cycles [ 43 - 45 ].…”
Section: Circadian Modulation Of Diseasementioning
confidence: 99%
“…Informal caregivers have reported having severe back pain due to alterations in the trunk muscle extensor strength [8,20], and other osteomuscular disorders [4]. At the psychological level, it has been found that informal caregivers experience high levels of subjective burden, distress, and a wide variety of psychological disorders [5,13,21,[24][25][26][27][28][29], as well as sleep problems [30][31][32]. In addition, as part of their role, caregivers also suffer other symptoms such as hostility, aggression, somatization, irritability, hallucinations, delusions, restlessness, and disinhibition [2,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%